2017
DOI: 10.3389/fnhum.2017.00567
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Diffusion Tensor Imaging-Based Assessment of Tract Alterations: An Application to Amyotrophic Lateral Sclerosis

Abstract: Objective: The potential of magnetic resonance imaging (MRI) as a technical biomarker for cerebral microstructural alterations in neurodegenerative diseases is under investigation. In this study, a framework for the longitudinal analysis of diffusion tensor imaging (DTI)-based mapping was applied to the assessment of predefined white matter tracts in amyotrophic lateral sclerosis (ALS), as an example for a rapid progressive neurodegenerative disease.Methods: DTI was performed every 3 months in six patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
0
27
0
1
Order By: Relevance
“…In addition, disease duration of the 3.0 T PLS sample was significantly higher than the 1.5 T PLS sample. However, although the ALS-associated slope of FA alterations over time has been reported at the individual level ( Baldaranov et al, 2017 ), only a weak correlation could be shown at the group level ( Kassubek et al, 2014 ). Still, the higher disease duration in the 3.0 T PLS patient sample may be responsible for the lower rate of not stageable PLS patients in the 3.0 T PLS patient sample compared to the 1.5 T PLS patient sample (11% for 3.0 T vs 34% for 1.5 T).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, disease duration of the 3.0 T PLS sample was significantly higher than the 1.5 T PLS sample. However, although the ALS-associated slope of FA alterations over time has been reported at the individual level ( Baldaranov et al, 2017 ), only a weak correlation could be shown at the group level ( Kassubek et al, 2014 ). Still, the higher disease duration in the 3.0 T PLS patient sample may be responsible for the lower rate of not stageable PLS patients in the 3.0 T PLS patient sample compared to the 1.5 T PLS patient sample (11% for 3.0 T vs 34% for 1.5 T).…”
Section: Discussionmentioning
confidence: 93%
“…A study with 65 DTI scans from ALS patients and healthy controls with several follow-up measurements ( Baldaranov et al, 2017 ) showed an FA decrease in the CST that correlated with the revised ALS functional rating scale (ALS-FRS-R – Cedarbaum et al, 1999 ). In other studies, both the clinical severity as assessed by the slope of the ALS-FRS-R and the disease duration significantly correlated with the resulting staging scheme ( Kassubek et al, 2014 , 2018b ).…”
Section: In Vivo Transfer Of the Staging Conceptmentioning
confidence: 99%
“…Brain network analyses have contributed valuable insights into cerebral pathology in vivo and have been extensively applied to various neurodegenerative conditions . With increasing availability of noninvasive imaging data for brain structure, including diffusion tensor imaging (DTI), the research area of network neuroscience is able to extend the focus from cross‐sectional comparison studies toward the longitudinal development of brain disorders . However, the step toward predicting individual disease progression has yet to be unraveled.…”
mentioning
confidence: 99%